Development of Introduction to Linguistics’ Textbook for English Education Students University of Muhammadiyah Gresik - Batubara, Riska Widiyanita; Batubara, Amrin; Ardiyansah, Tri Yuli (Journal of English Teaching, Literature, and Applied Linguistics, 2021)
This study aimed to develop textbook for Introduction to Linguistics subject for 4th semester English Department students in the Faculty of Teacher Training and Education University of Muhammadiyah Gresik. Students who take this subject often find it challenging to understand the materials as they are not equipped with the textbook; therefore this study was conducted. This study was a Research and Development (R&D) study on the textbook of Introduction to Linguistics, using the Four-D (4D) model, which includes (1) Define, (2) Design, (3) Develop and (4) Disseminate. Data was collected through observation, questionnaire as well as unstructured interview. The results showed that textbook draft of Introduction to Linguistics has suited the percentage of media validation from material and teaching media experts by 93.3% and 95.4%, respectively. From the validation result, it is concluded that this textbook can be perfected and used.